ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENIPUAN YANG DILAKUKAN OLEH NOTARIS (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 66 PK/PID/2017) - VANESSA WIJAYA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Henry Sinaga, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum In doing his job, a Notary should be guided by laws, the Code of Ethics, and morality since violation against his tasks will harm people. When he makes a defective deed because of his fault, either intentionally or unintentionally, he has to be liable for it. The implementation of law in the field shows that there is still intentional fault or negligence done by a Notary so that deeds contain fraud criminal act. The problems of the research are how about the regulation of fraud criminal act in the Penal Code, how about the legal reasons of the Supreme Court for a Notary’s fraud criminal act in the Ruling No. 66 PK/PID/217, ad how about a Notary’s liability for his fraud criminal act. The result of the research shows that fraud criminal act is regulated in Article 378 of the Penal Code which, in this research, is related to Article 55 of the Penal Code. The judges’ legal consideration in the Supreme Court’s Ruling No. 66 PK/PID/217 is that it has met the elements of criminal act in Article 378 of the Penal Code since the Notary has committed fraud and a series of deceit. He, therefore, is liable for what he has done and a criminal sanction has to be imposed on him by his imprisonment.Keywords: Criminal Liability, Notary, Fraud Criminal Act